2024
DOI: 10.1183/16000617.0166-2023
|View full text |Cite
|
Sign up to set email alerts
|

REM sleep obstructive sleep apnoea

Maria R. Bonsignore,
Emilia Mazzuca,
Pierpaolo Baiamonte
et al.

Abstract: Obstructive sleep apnoea (OSA) can occur in both rapid eye movement (REM) and non-REM sleep or be limited to REM sleep, when the upper airway is most prone to collapse due to REM sleep atonia. Respiratory events are usually longer and more desaturating in REM than in NREM sleep. The prevalence of REM OSA is higher in women than in men and REM OSA usually occurs in the context of mild–moderate OSA based on the apnoea–hypopnoea index calculated for the entire sleep study. Studies have highlighted some detrimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 120 publications
0
0
0
Order By: Relevance
“…Furthermore, a few studies have shown that OSA during the REM sleep phase may be particularly relevant in the context of pregnancy, as this phase entails increased relaxation of the upper airway muscles, thereby heightening the risk of obstructive apneas. In addition, REM OSA is usually associated with longer respiratory events and higher hypoxia than OSA during non-REM sleep [44]. Also, REM OSA has been linked to higher GDM risk [20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a few studies have shown that OSA during the REM sleep phase may be particularly relevant in the context of pregnancy, as this phase entails increased relaxation of the upper airway muscles, thereby heightening the risk of obstructive apneas. In addition, REM OSA is usually associated with longer respiratory events and higher hypoxia than OSA during non-REM sleep [44]. Also, REM OSA has been linked to higher GDM risk [20].…”
Section: Discussionmentioning
confidence: 99%
“…This observation led to the hypothesis that longer event durations might indicate a higher hypoxemic burden, whereby CPAP therapy could potentially negate the protective effects of ischemic preconditioning in patients with existing cardiac risks ( 10 ), which aligns with a recent Veterans Health Administration study (1999–2020) among 72,036 veterans hospitalized for acute myocardial infarction, revealing that those with OSA experienced the lowest in-hospital mortality ( 11 ). Also, extended apnea durations may indicate a rapid eye movement (REM)–predominant OSA phenotype and/or endotype, which is characterized by longer apnea duration and has been linked to increased CVD risk ( 12 , 13 ). The lack of electroencephalography in sleep testing in Cohen and colleagues’ study hindered the assessment of how events from specific sleep stages (such as REM sleep–related vs. non–REM sleep–related OSA) influenced recurrent CVD events in participants.…”
mentioning
confidence: 99%